2014
DOI: 10.1016/j.cois.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The mosquito microbiota influences vector competence for human pathogens

Abstract: The midgut of insect vectors of human disease contains not only pathogens harmful to human health, but also a diverse microbiota. This microbiota can influence insects’ susceptibility to human pathogens, and the capacity to transmit them, through different mechanisms. Understanding the interaction between the vector, its microbiota and transmitted pathogens will provide novel opportunities to limit disease transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 103 publications
(80 reference statements)
1
171
0
3
Order By: Relevance
“…Arthropods are no exception and the literature is rich with examples of various arthropod-microbiota associations that modulate essential aspects of the arthropod life cycle including reproductive fitness, survival and vectorial competence [4-6]. Arthropods vector human, livestock and plant pathogens worldwide and pose a tremendous health and economic burden [7, 8].…”
Section: Tick Microbiome: Old Players Hold New Hopementioning
confidence: 99%
“…Arthropods are no exception and the literature is rich with examples of various arthropod-microbiota associations that modulate essential aspects of the arthropod life cycle including reproductive fitness, survival and vectorial competence [4-6]. Arthropods vector human, livestock and plant pathogens worldwide and pose a tremendous health and economic burden [7, 8].…”
Section: Tick Microbiome: Old Players Hold New Hopementioning
confidence: 99%
“…During the mosquito infection cycle, Plasmodium parasites encounter a variety of resident microbiota both in the mosquito midgut and other tissues. Numerous studies have shown that certain species of bacteria can inhibit Plasmodium development 24 . For example, Enterobacter bacteria that reside in the Anopheles midgut can inhibit the development of Plasmodium parasites prior to their invasion of the midgut epithelium 5, 6 .…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have investigated the effect of the bacterial microbiome on Plasmodium infection in Anopheles mosquitoes [24,25], it is also evident the microbiome modulates arboviral vector competence. Most studies employ antibiotic treatment or reinfection of cultured microbes to perturb the microbiome.…”
Section: Influence On Vector Competencementioning
confidence: 99%